2020
DOI: 10.1002/admt.202000261
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of a Novel Series of Geometrically Complex Intravaginal Rings with Digital Light Synthesis

Abstract: Intravaginal rings (IVRs) represent a sustained‐release approach to drug delivery and have long been used and investigated for hormones and microbicides delivery. For decades, IVRs have been manufactured by injection molding and hot‐melt extrusion with very limited design and material capabilities. Additive manufacturing (AM), specifically digital light synthesis (DLS), represents an opportunity to harness the freedom of design to expand control and tunability of drug release properties from IVRs. A novel appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 51 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Additive manufacturing (3D printing) offers an opportunity to further improve upon IVR fabrication by expanding IVR design scope, thus allowing for greater control on drug release kinetics and the ability to achieve complete drug release from the IVR. To our knowledge, all MPT IVRs in development incorporate standard injection molding techniques to some extent, and there are only three published attempts to 3D print IVRs [ 127 , 128 , 129 ] based on an extensive literature search. For instance, Fu et al demonstrated one of the first attempts to 3D print an IVR for the contraceptive delivery of progesterone [ 127 ].…”
Section: Vaginally Delivered Mptsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additive manufacturing (3D printing) offers an opportunity to further improve upon IVR fabrication by expanding IVR design scope, thus allowing for greater control on drug release kinetics and the ability to achieve complete drug release from the IVR. To our knowledge, all MPT IVRs in development incorporate standard injection molding techniques to some extent, and there are only three published attempts to 3D print IVRs [ 127 , 128 , 129 ] based on an extensive literature search. For instance, Fu et al demonstrated one of the first attempts to 3D print an IVR for the contraceptive delivery of progesterone [ 127 ].…”
Section: Vaginally Delivered Mptsmentioning
confidence: 99%
“…More recently, Janusziewicz et al reported on 3D-printed IVRs fabricated using digital light synthesis or continuous liquid interface production (CLIP™) [ 129 , 130 ]. This method utilizes a photosensitive resin that selectively solidifies upon exposure to ultra-violet (UV) light via free radical photopolymerization mechanisms to generate the final product [ 130 ].…”
Section: Vaginally Delivered Mptsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it operates at room temperature; hence, it avoids the risk of thermal degradation of drugs [ 50 ]. Thus far, vat photopolymerisation 3D printing techniques have been explored to prepare pharmaceutical products for various drug delivery purposes, including oral dosage forms [ 51 , 52 , 53 ], nose patches [ 45 ], microneedles [ 54 , 55 , 56 ], intravaginal rings [ 57 ], dental [ 58 ], bladder devices [ 59 ] and hearing aids [ 60 ].…”
Section: Introductionmentioning
confidence: 99%